Political Imaging Techniques Carried Out by Baitul Muslimin Indonesia (BAMUSI) in Increasing Public Political Support for PDI Perjuangan Medan City - Sutarto, Sutarto; Lubis, Suwardi; Katimin, Katimin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
BAMUSI is a new breakthrough for PDI Perjuangan to restore the negative stigmatization directed at PDI Perjuangan so far. BAMUSI is here to build a good image of PDI Perjuangan which has only been buzzing and narrating as a national and religious based party. BAMUSI will make a movement towards Islamic understanding that is rahmatan lil 'alamin bagi for the nation. Political imaging techniques carried out by BAMUSI in increasing the political support of the people of PDI Perjuangan Medan, namely to carry out social services: Social service activities carried out by BAMUSI Medan City is an accurate strategy in approaching and touching the hearts of Medan people in fostering community trust. Delivering Assistance: The political imaging technique carried out by BAMUSI Medan City in increasing community political support for PDI Perjuangan is by channeling aid.